Hukum hukum fiqih Islam: yang berkembang dalam kalangan Ahlus Sunnah - T.M. Hasbi Ash_Shiddieqy (Bulan Bintang, 1978)
ir,c.1-3/ir,c.4/ir,c.5/ast c.6-7/ir,c.8/ir,c.9/ir,c.10/oen, c.11/ir,c.12/oen, c.13